Ultrathin electromagnetic oven silica gel protection pad and preparation method thereof

By using specific formulas and heat treatment technologies in induction cooker silicone protective pads, combining biomass carbon nanoparticles and silica microspheres, the problems of easy damage to silicone pads and hazards of glass fibers are solved, achieving high mechanical strength, thermal conductivity and resistance Abrasive effect.

CN119463497APending Publication Date: 2025-02-18FENGYANG JIASONG NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411422335.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing induction cooker silicone protective pad is prone to damage during frequent scrubbing, and the addition of glass fibers has potential harm to the human body, which limits its use.

Method used

Use ultra-thin silicone protective pad composed of dimethyl silicone rubber, methylvinyl silicone rubber, silica microspheres, biomass char nanoparticles, calcium stearate and sodium gluconate, through specific heat treatment and nanofillers The use of the product enhances its thermal conductivity, wear resistance and oil stain resistance.

Benefits of technology

It realizes the high mechanical strength, thermal conductivity and wear resistance of the silicone pad, and has antibacterial, hydrophobic and oleophobic effects, improving its fatigue resistance and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081178080000121
    Figure BDA0005081178080000121
Patent Text Reader

Abstract

The invention relates to an ultrathin induction cooker silica gel protection pad and a preparation method thereof, and belongs to the technical field of silica gel products, the ultrathin induction cooker silica gel protection pad is prepared from the following raw materials by weight: 40-50 parts of dimethyl silicone rubber, 35-45 parts of methyl vinyl silicone rubber, 10-15 parts of silica microspheres, 15-20 parts of biomass charcoal nanoparticles, 2.0-2.5 parts of 2, 5-dimethyl-2, 5-bis (2, 5-dimethyl-2, 5-bis (2, 5-bis (2, 5-bis (2, 5-bis (2, 5-bis (2, 5-bis (2, 5-bis (2, 5-bis (2, 5-bis (2, 5-bis (2, 5-bis (2, 5 The silica gel pad has the advantages that the silica gel pad is excellent in thermal conductivity and wear resistance and has antibacterial, hydrophobic and oleophobic effects by combining the silica microspheres with the biomass charcoal nanoparticles loaded with the nanofiller, and the fatigue resistance stability of the silica gel pad is improved by performing different heat treatments on the biomass charcoal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silicone products, and in particular relates to an ultra-thin induction cooker silicone protective pad and a preparation method thereof. Background Art

[0002] Existing induction cooker panels are generally made of glass, but the heat resistance of glass is too poor, which poses a safety hazard. The difference between the induction cooker silicone protective pad and glass is heat resistance. Silicone is a highly elastic polymer material with reversible deformation, strong heat resistance, and can return to its original state after the external force is removed. It is also non-toxic, odorless, high temperature resistant, cheap, and not easy to stick. However, the mechanical properties of silicone are low, and the silicone pad will be damaged during frequent scrubbing. Previous studies have increased its mechanical properties by adding glass fiber, but glass fiber is more harmful to the human body. The frequent use of the silicone protective pad for the induction cooker can easily expose the glass fiber for long-term use, which may cause damage to the eyes, skin, and respiratory tract, thereby limiting the use of silicone pads on induction cookers. Summary of the invention

[0003] The purpose of the present invention is to provide an ultra-thin induction cooker silicone protective pad and a preparation method thereof in order to solve the above problems.

[0004] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0005] The invention provides an ultra-thin induction cooker silicone protective pad, which is made of the following raw materials by weight: 40-50 parts of dimethyl silicone rubber, 35-45 parts of methyl vinyl silicone rubber, 10-15 parts of silicon dioxide microspheres, 15-20 parts of biomass carbon nanoparticles, 2.0-2.5 parts of double 25, 1-2 parts of calcium stearate, and 0.5-1 part of sodium gluconate;

[0006] The preparation process of biochar nanoparticles is as follows:

[0007] The biochar is washed with alkaline water and then impregnated with a catalyst; after drying, low-temperature heat treatment and continuous high-temperature heat treatment are sequentially performed in an oxygen-free environment, and the treated product is washed with acid water; the treated biochar is ground into powder and dispersed with nanofillers in ethylene glycol and stirred, and ultrasonic and heat treatments are sequentially performed, followed by centrifugation, and washed with ethanol and deionized water for multiple times, and finally vacuum dried to obtain biochar nanoparticles.

[0008] As a further optimization scheme of the present invention, the pore size of the silica microspheres is 200-300 nm.

[0009] As a further optimization scheme of the present invention, the preparation process of the silica microspheres is to disperse the mesoporous silica microspheres in a sodium chloride solution at room temperature, stir ultrasonically, filter and vacuum dry, and then perform a two-stage heating treatment. In the first stage, the temperature is raised to 230-250°C and maintained for 1 hour, then raised to 650-700°C and maintained for 1 hour, and after natural cooling, washed with ethanol and deionized water for multiple times to obtain silica microspheres.

[0010] As a further optimization scheme of the present invention, the biomass charcoal is obtained by washing, drying and then carbonizing the biomass material at high temperature, and the biomass material includes corn stalks, rice husks, peanut shells, bamboo and trees.

[0011] As a further optimization scheme of the present invention, the alkaline water is a sodium hydroxide aqueous solution with a mass fraction of 10-15wt%, and the catalyst is ammonium sulfate with a mass fraction of 10-15wt%.

[0012] As a further optimization scheme of the present invention, the oxygen-free environment is nitrogen or argon; the low-temperature heat treatment temperature is 200-250°C and the treatment time is 30-45min; the continuous high-temperature heat treatment is specifically, treating at a temperature of 700-900°C for 30-45min, and then treating at a temperature of 1000-1500°C for 45-60min; the acid water is a hydrochloric acid aqueous solution with a mass fraction of 10-15wt%.

[0013] As a further optimization scheme of the present invention, the mass ratio of biomass carbon powder to nanofiller is (5-10):1, and the nanofiller is composed of equal masses of nano zinc oxide, nano boron nitride and nano aluminum nitride.

[0014] As a further optimization scheme of the present invention, the temperature of the heating reaction after ultrasound is 150° C.-200° C., and the processing time is 2-4 hours.

[0015] The present invention also provides a method for preparing the ultra-thin induction cooker silicone protective pad, comprising the following steps:

[0016] (1) mixing silica microspheres with biomass carbon nanoparticles in an ethanol solution, removing ethanol after mixing, grinding and mixing methyl vinyl silicone rubber and dimethyl silicone oil under heating, adding the mixture of silica microspheres and biomass carbon nanoparticles to the mixture under heating, adding calcium stearate and sodium gluconate after uniform dispersion, stirring at high speed and standing for 1-3 hours to obtain a silica gel base material;

[0017] (2) vacuuming the silica gel base material to completely extract the bubbles in the silica gel base material;

[0018] (3) After the silicone base material is poured into a mixer and kneaded into a soft state, dichloroethylene is added and kneaded continuously, and then the soft kneaded material is put into a mold, vulcanized by hot air and then pressurized to obtain the silicone protective pad after cooling.

[0019] As a further optimization scheme of the present invention, the vulcanization temperature is 200-230° C., and the vulcanization time is 8-10 min.

[0020] The beneficial effects of the present invention are:

[0021] (1) The present invention combines silica microspheres with biochar nanoparticles loaded with nanofillers, so that the silicone pad has excellent thermal conductivity and wear resistance, and also has antibacterial, hydrophobic and oleophobic effects. The present invention increases the fatigue resistance and stability of the silicone pad by subjecting the biochar to different heat treatments.

[0022] (2) The present invention processes the biochar to make the biochar nanoparticles more dispersed, enhance the interaction force with silica microspheres and silicone rubber, and increase the mechanical strength of the silicone pad; and the macroporous silica microspheres prepared by mesoporous silica microspheres work together with the biochar nanoparticles. Compared with directly using macroporous silica microspheres, mesoporous silica microspheres and silica sol, the residual silanol on the surface of the silica gel is eliminated to the greatest extent, which helps to improve the compatibility and loading effect of the biochar nanoparticles and silicone rubber, so that the silicone pad can retain its stability while having high mechanical strength, and also has excellent anti-oil performance.

[0023] (3) Based on the use of silica microspheres and biochar nanoparticles, the present invention effectively blocks the surface pores of the silica microsphere fibers and the gaps between the silicone rubber by loading the silica microspheres with biochar nanoparticles of a specific particle size ratio, thereby preventing the adhesion and penetration of oil stains and improving the mechanical strength of the silicone pad. DETAILED DESCRIPTION

[0024] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.

[0025] 1. Materials

[0026] Unless otherwise specified, the methods used in the present invention are conventional methods known to those skilled in the art, and the reagents and other materials used are commercially available products unless otherwise specified.

[0027] Biomass charcoal is obtained by washing and drying biomass materials and then carbonizing them at high temperature. The biomass materials include but are not limited to corn stalks, rice husks, peanut shells, bamboo, and trees. Different biomasses have different high-temperature carbonization temperatures, ranging from 300 to 900° C. The following embodiments of the present invention all use rice husk biomass charcoal.

[0028] 2. Methods

[0029] Example 1

[0030] The ultra-thin induction cooker silicone protective pad provided in this embodiment is made of the following raw materials by weight: 50 parts of dimethyl silicone rubber, 35 parts of methyl vinyl silicone rubber, 10 parts of silica microspheres, 15 parts of biomass carbon nanoparticles, 2.0 parts of di-25, 1 part of calcium stearate, and 0.5 parts of sodium gluconate;

[0031] in:

[0032] Preparation of silica microspheres: 1 kg of mesoporous silica microspheres (10-50 nm) were dispersed into 10 L of 5% sodium chloride solution at room temperature, stirred for 3 h and ultrasonicated, filtered and vacuum dried for 2 h, and then transferred to a high-temperature box furnace for a two-stage heating treatment. In the first stage, the temperature was uniformly raised to 235°C and maintained for 1 h, then uniformly raised to 700°C and maintained for 1 h. After naturally cooling to room temperature, the temperature was washed 3 times with ethanol and deionized water, and dried to obtain silica microspheres with a pore size of 200-300 nm.

[0033] Preparation of biochar nanoparticles:

[0034] The biochar was washed with a 12wt% sodium hydroxide aqueous solution and then impregnated with a 12wt% ammonium sulfate catalyst for 45 minutes; after drying at 50-60°C, it was transferred to a box-type atmosphere furnace and treated at 250°C for 30 minutes in a nitrogen environment. After cooling, the temperature was raised to 900°C for 30 minutes, and then the temperature was raised to 1500°C for 45 minutes. After cooling to room temperature, it was taken out and the treated material was washed twice with a 12wt% hydrochloric acid aqueous solution; the treated material was ground into powder and dispersed in ethylene glycol with nanofillers (composed of equal masses of nano zinc oxide, nano boron nitride and nano aluminum nitride) at a mass ratio of 10:1 and stirred, and ultrasonic and 150°C heating treatments were performed in sequence for 2 hours, then centrifuged, washed 3 times with ethanol and deionized water, and finally vacuum dried to obtain biochar nanoparticles. The biomass carbon nanoparticles are processed by density gradient ultracentrifugation to obtain biomass carbon nanoparticles with a particle size of 10-100 nm, wherein the nanoparticles with a particle size range of 45-90 nm account for at least 60% of the total mass.

[0035] The preparation method of the silicone protective pad is as follows:

[0036] (1) Mixing silica microspheres with biomass carbon nanoparticles in an ethanol solution and stirring them ultrasonically, removing ethanol by washing and filtering after mixing to obtain a mixture, grinding and mixing methyl vinyl silicone rubber and dimethyl silicone oil at 150° C., adding the mixture of silica microspheres and biomass carbon nanoparticles to the mixture under heating, adding calcium stearate and sodium gluconate after uniform dispersion, stirring at high speed and standing for 1-3 hours to obtain a silica gel base material; stirring at high speed and standing for 3 hours to obtain a silica gel base material;

[0037] (2) vacuuming the silica gel base material to completely extract the bubbles in the silica gel base material;

[0038] (3) After the silicone base material is poured into a mixer and refined into a soft state, bis(225) is added and continued to be mixed, and then the soft mixture is put into a mold and vulcanized by hot air at a temperature of 200°C and a vulcanization time of 8.5 minutes. Then, it is pressurized and cooled to obtain a silicone protective pad with a thickness of 2 mm.

[0039] Example 2

[0040] The ultra-thin induction cooker silicone protective pad provided in this embodiment is made of the following raw materials by weight: 45 parts of dimethyl silicone rubber, 40 parts of methyl vinyl silicone rubber, 15 parts of silica microspheres, 20 parts of biochar nanoparticles, 2.0 parts of di-25, 1 part of calcium stearate, and 0.5 parts of sodium gluconate;

[0041] in:

[0042] Preparation of silica microspheres: 1 kg of mesoporous silica microspheres (10-50 nm) were dispersed into 10 L of 5% sodium chloride solution at room temperature, stirred for 3 h and ultrasonicated, filtered and vacuum dried for 2 h, and then transferred to a high-temperature box furnace for a two-stage heating treatment. In the first stage, the temperature was uniformly raised to 240°C and maintained for 1 h, then uniformly raised to 700°C and maintained for 1 h. After naturally cooling to room temperature, the temperature was washed 3 times with ethanol and deionized water, and dried to obtain silica microspheres with a pore size of 200-300 nm.

[0043] Preparation of biomass carbon nanoparticles: The biomass carbon is washed with a sodium hydroxide aqueous solution with a mass fraction of 14wt% and then impregnated with an ammonium sulfate catalyst with a mass fraction of 12wt% for 45min; after drying at 50-60℃, it is transferred to a box-type atmosphere furnace, and treated at 200℃ for 45min in a nitrogen environment. After cooling, the temperature is increased to 800℃ for 40min, and then the temperature is increased to 1300℃ for 55min. After cooling to room temperature, it is taken out, and the treated material is washed twice with a hydrochloric acid aqueous solution with a mass fraction of 14wt%; the treated material is ground into powder and dispersed in ethylene glycol with nanofillers (composed of equal masses of nano zinc oxide, nano boron nitride and nano aluminum nitride) at a mass ratio of 10:1 and stirred, and ultrasonic and 150℃ heating treatments are performed in sequence for 2h, then centrifuged, washed 3 times with ethanol and deionized water, and finally vacuum dried to obtain biomass carbon nanoparticles. The biomass carbon nanoparticles are processed by density gradient ultracentrifugation to obtain biomass carbon nanoparticles with a particle size of 10-100 nm, wherein the nanoparticles with a particle size range of 45-90 nm account for at least 75% of the total amount.

[0044] The preparation method of the silicone protective pad is as follows:

[0045] (1) Mixing silica microspheres with biomass carbon nanoparticles in an ethanol solution and stirring them ultrasonically, removing ethanol by washing and filtering after mixing to obtain a mixture, grinding and mixing methyl vinyl silicone rubber and dimethyl silicone oil at 150° C., adding the mixture of silica microspheres and biomass carbon nanoparticles to the mixture under heating, adding calcium stearate and sodium gluconate after uniform dispersion, stirring at high speed and standing for 1-3 hours to obtain a silica gel base material; stirring at high speed and standing for 3 hours to obtain a silica gel base material;

[0046] (2) vacuuming the silica gel base material to completely extract the bubbles in the silica gel base material;

[0047] (3) After the silicone base material is poured into a mixer and refined into a soft state, double 25 is added and continued to be mixed, and then the soft mixture is put into a mold and vulcanized by hot air at a temperature of 200°C and a vulcanization time of 8.5 minutes. Then, it is pressurized and cooled to obtain a silicone protective pad with a thickness of 2 mm.

[0048] Example 3

[0049] The ultra-thin induction cooker silicone protective pad provided in this embodiment is made of the following raw materials by weight: 45 parts of dimethyl silicone rubber, 45 parts of methyl vinyl silicone rubber, 15 parts of silica microspheres, 20 parts of biochar nanoparticles, 2.0 parts of di-25, 1 part of calcium stearate, and 1 part of sodium gluconate;

[0050] in:

[0051] Preparation of silica microspheres: 1 kg of mesoporous silica microspheres (10-50 nm) were dispersed into 10 L of 5% sodium chloride solution at room temperature, stirred for 3 h and ultrasonicated, filtered and vacuum dried for 2 h, and then transferred to a high-temperature box furnace for a two-stage heating treatment. In the first stage, the temperature was uniformly raised to 240°C and maintained for 1 h, then uniformly raised to 700°C and maintained for 1 h. After naturally cooling to room temperature, the temperature was washed 3 times with ethanol and deionized water, and dried to obtain silica microspheres with a pore size of 200-300 nm.

[0052] Preparation of biomass carbon nanoparticles: The biomass carbon is washed with a sodium hydroxide aqueous solution with a mass fraction of 12wt% and then impregnated with an ammonium sulfate catalyst with a mass fraction of 10wt% for 45min; after drying at 50-60°C, it is transferred to a box-type atmosphere furnace, and treated at 200°C for 45min in a nitrogen environment. After cooling, the temperature is increased to 700°C for 45min, and then the temperature is increased to 1200°C for 60min. After cooling to room temperature, it is taken out, and the treated material is washed twice with a hydrochloric acid aqueous solution with a mass fraction of 12wt%; the treated material is ground into powder and dispersed in ethylene glycol with nanofillers (composed of equal masses of nano zinc oxide, nano boron nitride and nano aluminum nitride) at a mass ratio of 10:1 and stirred, and ultrasonic and 150°C heating treatments are performed in sequence for 2h, then centrifuged, washed 3 times with ethanol and deionized water, and finally vacuum dried to obtain biomass carbon nanoparticles. The biomass carbon nanoparticles are processed by density gradient ultracentrifugation to obtain biomass carbon nanoparticles with a particle size of 10-100 nm, wherein the nanoparticles with a particle size range of 45-90 nm account for at least 85% of the total amount.

[0053] The preparation method of the silicone protective pad is as follows:

[0054] (1) Mixing silica microspheres with biomass carbon nanoparticles in an ethanol solution and stirring them ultrasonically, removing ethanol by washing and filtering after mixing to obtain a mixture, grinding and mixing methyl vinyl silicone rubber and dimethyl silicone oil at 150° C., adding the mixture of silica microspheres and biomass carbon nanoparticles to the mixture under heating, adding calcium stearate and sodium gluconate after uniform dispersion, stirring at high speed and standing for 1-3 hours to obtain a silica gel base material; stirring at high speed and standing for 3 hours to obtain a silica gel base material;

[0055] (2) vacuuming the silica gel base material to completely extract the bubbles in the silica gel base material;

[0056] (3) After the silicone base material is poured into a mixer and refined into a soft state, double 25 is added and continued to be mixed, and then the soft mixture is put into a mold and vulcanized by hot air at a temperature of 200°C and a vulcanization time of 8.5 minutes. Then, it is pressurized and cooled to obtain a silicone protective pad with a thickness of 2 mm.

[0057] Comparative Example 1

[0058] The silicone pad is made of the following raw materials by weight: 45 parts of dimethyl silicone rubber, 45 parts of methyl vinyl silicone rubber, 15 parts of silicon dioxide microspheres, 20 parts of nanoparticles, 2.5 parts of bis(25-25), 1 part of calcium stearate, and 1 part of sodium gluconate;

[0059] Among them, the preparation of nanoparticle one: grind the biomass charcoal into powder and disperse it with nanofiller (composed of equal mass of nano zinc oxide, nano boron nitride and nano aluminum nitride) in ethylene glycol at a mass ratio of 10:1 and stir, then perform ultrasonic treatment and heat treatment at 150°C for 2h in sequence, then centrifuge, wash with ethanol and deionized water for 3 times, and finally vacuum dry to obtain nanoparticle one.

[0060] The remaining raw materials and preparation method are the same as in Example 3.

[0061] Comparative Example 2

[0062] The silicone pad is made of the following raw materials by weight: 45 parts of dimethyl silicone rubber, 45 parts of methyl vinyl silicone rubber, 15 parts of silicon dioxide microspheres, 20 parts of nanoparticles, 2.5 parts of dimethicone, 1 part of calcium stearate, and 1 part of sodium gluconate;

[0063] Among them, the preparation of nanoparticles 1: grind the biomass charcoal into nano-scale powder, wash it with ethanol and deionized water for 3 times, and vacuum dry it to obtain nanoparticles 2.

[0064] The remaining raw materials and preparation method are the same as in Example 3.

[0065] Comparative Example 3

[0066] The silicone pad is made of the following raw materials by weight: 45 parts of dimethyl silicone rubber, 45 parts of methyl vinyl silicone rubber, 15 parts of silicon dioxide microspheres, 20 parts of nanoparticles tris, 2.5 parts of bisulfite, 1 part of calcium stearate, and 1 part of sodium gluconate;

[0067] Among them, nanoparticle three is composed of equal masses of nano zinc oxide, nano boron nitride and nano aluminum nitride, and the particle size ranges from 100 to 500 nm.

[0068] The remaining raw materials and preparation method are the same as in Example 3.

[0069] Comparative Example 4

[0070] The silicone pad is made of the following raw materials by weight: 45 parts of dimethyl silicone rubber, 45 parts of methyl vinyl silicone rubber, 15 parts of silicon dioxide microspheres, 20 parts of biomass carbon nanoparticles, 2.5 parts of dimethicone, 1 part of calcium stearate, and 1 part of sodium gluconate;

[0071] Among them, the silica microspheres directly use mesoporous silica microspheres with a pore size range of 10-50nm.

[0072] The remaining raw materials and preparation method are the same as in Example 3.

[0073] Comparative Example 5

[0074] The silicone pad is made of the following raw materials by weight: 45 parts of dimethyl silicone rubber, 45 parts of methyl vinyl silicone rubber, 15 parts of silicon dioxide microspheres, 20 parts of biomass carbon nanoparticles, 2.5 parts of dimethicone, 1 part of calcium stearate, and 1 part of sodium gluconate;

[0075] The silica microspheres are directly commercially available macroporous silica microspheres with a pore size range of 300-500 nm.

[0076] The remaining raw materials and preparation method are the same as in Example 3.

[0077] 3. Test Verification

[0078] The silicone protective pads prepared in Examples 1-3 and Comparative Examples 1-5 were cut into suitable sizes as test samples, and Example 3 of the previous study with the publication number CN108047721B was used as the control group to conduct the following tests:

[0079] Thermal conductivity: The thermal conductivity of each sample was measured using a NETZSCH LFA427 laser thermal conductivity meter, and the average value was taken after 5 measurements.

[0080] Wear resistance: A circular grinding wheel was used to contact each sample, with a load of 800g and a rotation speed of 100rpm for wear test. During the wear process, the surface temperature of the silicone pad sample was always kept below 50°C until obvious cracks appeared on the surface of the silicone pad sample, and the number of revolutions was recorded;

[0081] Tear strength: Use WDS series universal testing machine to measure the tear strength of each sample, and measure 5 times to get the average value;

[0082] Thermal fatigue resistance: Soak each sample in vegetable oil for 24 hours, take it out and wash it until there is no vegetable oil on the surface. After standing for 2 hours without oil leakage, put it into a constant temperature forced air drying oven at 240°C for 1 hour. After taking it out and cooling it, cycle the drying heating-cooling process for 100 times, and then measure its thermal conductivity and tear strength.

[0083] The test results are recorded in the following table:

[0084]

[0085] Note: ① is before the cycle; ② is after 100 cycles.

[0086] It can be seen from the above table that the thermal conductivity coefficients of Examples 1-3 are all stable at above 4.0, which can reach or even exceed the thermal conductivity effect of previously studied silicone products, and the tear strength is also slightly higher than that of previous silicone products. Without adding glass fiber, the present invention combines silica microspheres with biochar nanoparticles loaded with nanofillers, so that the silicone pad has excellent thermal conductivity, tear strength and wear resistance, while also having the antibacterial, hydrophobic and oleophobic effects of the nanofillers and biochar nanoparticles themselves.

[0087] It can be seen from the test data of each sample of Comparative Examples 2-3 that the thermal conductive filler component in the nanofiller is the factor that has the greatest impact on the thermal conductivity. The more the thermal conductive filler is added, the better the thermal conductivity is in the initial state. However, after 100 cycles, the thermal conductivity drops drastically, which shows that its thermal fatigue resistance is extremely poor. Moreover, compared with the control group, the thermal conductivity and tear strength of Examples 1-3 have a small performance decline after 100 cycles. It can be seen that the fatigue resistance stability of the control group is slightly poor. The present invention increases the fatigue resistance stability of the silicone pad by performing different heat treatments on the biochar.

[0088] It can be seen from the test results of each sample of Examples 1-3 and Comparative Examples 4-5 that the macroporous silica microspheres prepared by using mesoporous silica microspheres, in cooperation with biochar nanoparticles, can eliminate the residual silanol on the surface of silica gel to the greatest extent compared with directly using macroporous silica microspheres, mesoporous silica microspheres and silica sol, which helps to improve the compatibility and loading effect of biochar nanoparticles and silicone rubber, so that the silicone pad can retain its stability while having high mechanical strength, and also has excellent anti-oil performance.

[0089] Furthermore, it can be seen from Examples 1-3 that the present invention, based on the use of silica microspheres and biochar nanoparticles, can effectively block the surface pores of the silica microsphere fibers and the gaps between the silicone rubber, prevent the adhesion and penetration of oil stains, and enhance the mechanical strength of the silicone pad by loading the silica microspheres with biochar nanoparticles of a specific particle size ratio, that is, nanoparticles in the particle size range of 45-90nm account for at least 85% of the total.

[0090] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. An ultra-thin induction cooker silicone protective pad, characterized in that: It is made of the following raw materials by weight: 40-50 parts of dimethyl silicone rubber, 35-45 parts of methyl vinyl silicone rubber, 10-15 parts of silicon dioxide microspheres, 15-20 parts of biochar nanoparticles, 2.0-2.5 parts of dimethicone, 1-2 parts of calcium stearate, and 0.5-1 parts of sodium gluconate; The preparation process of biochar nanoparticles is as follows: The biochar is washed with alkaline water and then impregnated with a catalyst; after drying, low-temperature heat treatment and continuous high-temperature heat treatment are sequentially performed in an oxygen-free environment, and the treated product is washed with acid water; the treated biochar is ground into powder and dispersed with nanofillers in ethylene glycol and stirred, and ultrasonic and heat treatments are sequentially performed, followed by centrifugation, and washed with ethanol and deionized water for multiple times, and finally vacuum dried to obtain biochar nanoparticles.

2. The ultra-thin induction cooker silicone protective pad according to claim 1, characterized in that: The pore size of the silica microspheres is 200-300 nm.

3. The ultra-thin induction cooker silicone protective pad according to claim 2, characterized in that: The preparation process of the silica microspheres is as follows: at room temperature, the mesoporous silica microspheres are dispersed in a sodium chloride solution, stirred and ultrasonicated, vacuum dried after filtration, and then subjected to a two-stage heating treatment. In the first stage, the temperature is raised to 230-250° C. and maintained for 1 hour, and then raised to 650-700° C. and maintained for 1 hour. After natural cooling, the silica microspheres are washed multiple times with ethanol and deionized water to obtain the silica microspheres.

4. The ultra-thin induction cooker silicone protective pad according to claim 1, characterized in that: The biomass charcoal is obtained by washing, drying and then carbonizing the biomass materials at high temperature. The biomass materials include corn stalks, rice husks, peanut shells, bamboo and trees.

5. The ultra-thin induction cooker silicone protective pad according to claim 1, characterized in that: The alkaline water is a sodium hydroxide aqueous solution with a mass fraction of 10-15wt%, and the catalyst is ammonium sulfate with a mass fraction of 10-15wt%.

6. The ultra-thin induction cooker silicone protective pad according to claim 1, characterized in that: The oxygen-free environment is nitrogen or argon; the low-temperature heat treatment temperature is 200-250°C and the treatment time is 30-45 minutes; the continuous high-temperature heat treatment is specifically, treating at a temperature of 700-900°C for 30-45 minutes, and then treating at a temperature of 1000-1500°C for 45-60 minutes; the acid water is a hydrochloric acid aqueous solution with a mass fraction of 10-15wt%.

7. The ultra-thin induction cooker silicone protective pad according to claim 1, characterized in that: The mass ratio of biomass carbon powder to nano filler is (5-10):1, and the nano filler is composed of nano zinc oxide, nano boron nitride and nano aluminum nitride of equal mass.

8. The ultra-thin induction cooker silicone protective pad according to claim 1, characterized in that: The temperature of the heating reaction after ultrasound is 150°C-200°C, and the processing time is 2-4h.

9. A method for preparing the ultra-thin induction cooker silicone protective pad as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: (1) mixing silica microspheres with biomass carbon nanoparticles in an ethanol solution, removing ethanol after mixing, grinding and mixing methyl vinyl silicone rubber and dimethyl silicone oil under heating, adding the mixture of silica microspheres and biomass carbon nanoparticles to the mixture under heating, adding calcium stearate and sodium gluconate after uniform dispersion, stirring at high speed and standing for 1-3 hours to obtain a silica gel base material; (2) vacuuming the silica gel base material to completely extract the bubbles in the silica gel base material; (3) After the silicone base material is poured into a mixer and kneaded into a soft state, dichloroethylene is added and kneaded continuously, and then the soft kneaded material is put into a mold, vulcanized by hot air and then pressurized to obtain the silicone protective pad after cooling.

10. The method for preparing an ultra-thin induction cooker silicone protective pad according to claim 9, characterized in that: The vulcanization temperature is 200-230° C., and the vulcanization time is 8-10 minutes.

Citation Information

Patent Citations

  • A high-temperature resistant steam oven mat

    CN108047721B